Lung Adenocarcinoma Mutation Hotspot in Koreans: Oncogenic Mutation Potential of the TP53 P72R Single Nucleotide Polymorphism - Jae Ha BAEK; Kyu Bong CHO (Korean Journal of Clinical Laboratory Science, 2023)
This study aimed to identify new markers that cause lung adenocarcinoma by analyzing mutation hotspots for the top five genes with high mutation frequency in lung adenocarcinoma in Koreans by next generation sequencing (NGS) analysis. The association between TP53 mutation types and patterns with smoking, a major cause of lung cancer, was examined. The clinicopathological characteristics of lung adenocarcinoma patients with TP53 P72R SNPs were analyzed. In Korean lung adenocarcinoma cases, regardless of the smoking status, the TP53 P72R SNP was the most frequently occurring mutational hotspot, in which the nucleotide base was transversed from C to G, and the amino acid was substituted from proline to arginine at codon 72 of TP53. An analysis of the clinicopathological characteristics of lung adenocarcinoma cases with TP53 P72R SNP revealed no significant correlation with the patient's age, gender, smoking status, and tumor differentiation, but a significant correlation with low stage (P-value =0.026). This study confirmed an increase in TP53 rather than EGFR, which was reported as the most frequent mutations in lung adenocarcinoma in Koreans through NGS. Among them, TP53 P72R SNP is the most frequent regardless of smoking status.